Helmet continuous positive airway pressure vs. high flow nasal cannula oxygen in acute cardiogenic pulmonary oedema: a randomized controlled trial. Issue 10 (11th October 2021) - Osman, Adi; Via, Gabriele; Sallehuddin, Roslanuddin Mohd; Ahmad, Azma Haryaty; Fei, Sow Kai; Azil, Azlizawati; Mojoli, Francesco; Fong, Chan Pei; Tavazzi, Guido
Abstract: Aims : Non-invasive ventilation represents an established treatment for acute cardiogenic pulmonary oedema (ACPO) although no data regarding the best ventilatory strategy are available. We aimed to compare the effectiveness of helmet CPAP (hCPAP) and high flow nasal cannula (HFNC) in the early treatment of ACPO. Methods and results : Single-centre randomized controlled trial of patients admitted to the emergency department due to ACPO with hypoxemia and dyspnoea on face mask oxygen therapy. Patients were randomly assigned with a 1:1 ratio to receive hCPAP or HFNC and FiO2 set to achieve an arterial oxygen saturation >94%. The primary outcome was a reduction in respiratory rate; secondary outcomes included changes in heart rate, PaO2 /FiO2 ratio, Heart rate, Acidosis, Consciousness, Oxygenation, and Respiratory rate (HACOR) score, Dyspnoea Scale, and intubation rate. Data were collected before hCPAP/HFNC placement and after 1 h of treatment. Amongst 188 patients randomized, hCPAP was more effective than HFNC in reducing respiratory rate [−12 (95% CI; 11–13) vs. −9 (95% CI; 8–10), P  <   0.001] and was associated with greater heart rate reduction [−20 (95% CI; 17–23) vs. −15 (95% CI; 12–18), P  =   0.042], P/F ratio improvement [+149 (95% CI; 135–163) vs. +120 (95% CI; 107–132), P  =   0.003] as well as in HACOR scores [6 (0–12) vs. 4 (2–9), P  <   0.001] and Dyspnoea Scale [4 (1–7) vs. 3.5 (1–6), P  =   0.003]. No differences in intubation rate were noted ( P  =   0.321). Conclusion : Amongst patients with ACPO, hCPAP resulted in a greater short-term improvement in respiratory and hemodynamic parameters as compared with HFNC. Trial registration : Clinical trial submission: NMRR-17-1839-36966 (IIR). Registry name: Medical Research and Ethics Committee of Malaysia Ministry of Health. Clinicaltrials.gov identifier: NCT04005092. URL registry: https://clinicaltrials.gov/ct2/show/NCT04005092 . Graphical Abstract: